Fathers and Sons Catullan Echoes of Remembering and Forgetting in Vergil’s Aeneid - Somfai, Péter (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In Vergil’s Aeneid the problematics of remembering and forgetting emerge as an issue of essential importance: the Trojans – somewhat paradoxically – have to bring about both of them in order to be able to found a new native land in Italy. The matter in question emphatically occurs in two speeches of fathers given to their sons in the epic: in that of the shade of Anchises given to Aeneas in Book 5 and in that of Aeneas given to Ascanius in Book 12. These passages both recall the speech of Aegeus to Theseus in Catullus 64, in which the father aims to ‘program’ his son’s mind to remember his instructions. It will be of fundamental importance to observe the way the Catullan text presenting the failure of this kind of ‘mnemotechnical’ remembering encodes forgetting into the Vergilian passages mentioned above, by means of intertextual connections.